Herculaneum Uncovered A Conversation with Andrew Wallace-Hadrill. - Burton, Howard (Ideas Roadshow Conversations Ser., 2021)
This book is based on an in-depth filmed conversation between Howard Burton and Andrew Wallace-Hadrill, Director of Research and Honorary Professor of Roman Studies in the Faculty of Classics at the University of Cambridge. This wide-ranging conversation covers his extensive archeological work done in Herculaneum and Pompeii, the politics of excavation, life in the ancient Roman world, Roman Law, and more.This carefully-edited book includes an introduction, Historical Value, and questions for discussion at the end of each chapter. Howard Burton was the Founding Director of Canada's Perimeter I.